HEMATOLOGIC PROFILE OF LABORATORY RATS FED WITH BAKERY PRODUCTS - Katica, Muhamed; Gradascevic, Nedzad (International Journal of Research -GRANTHAALAYAH, 2017)
The laboratory rat, as important biomedical model, was often fed with unconventional diet usually made up of products from the bakery industry. Such diet consisted of insufficient caloric and nutritionally unbalanced meals could cause unreliable results in biomedical research. The study investigates the effects of malnutrition on the haematological profile of rats. The study is performed on Wistar male and female rats which were fed for 4 weeks exclusively with bakery products ad libidum. The following hematological parameters were observed in peripheral blood smears: red blood cell count, content of haemoglobin, haematocrit, MCV, MCH, MCHC, white blood cell count, differential blood count, diameter of red blood cells, as well as the presence of atypical forms of red blood cells. Despite there were no statistically significant differences in overall haematological results (p > 0.05, with > 0.05), the significant part of obtained results were below physiological limits (HGB, MCHC and MCH). Other haematological parameters, including white blood corpuscles were kept in physiological limits, except for mild neutrophils in males. Also, the forms of anulocytes and spherocytes were recorded in peripheral blood smears. The results indicated the beginning of normocytic hypochromic anaemia which was caused by unbalanced meals.